2009
DOI: 10.1002/pro.180
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte perturbation reveals conformational equilibria in spin‐labeled proteins

Abstract: Recent evidence suggests that proteins at equilibrium can exist in a manifold of conformational substates, and that these substates play important roles in protein function. Therefore, there is great interest in identifying regions in proteins that are in conformational exchange. Electron paramagnetic resonance spectra of spin-labeled proteins containing the nitroxide side chain (R1) often consist of two (or more) components that may arise from slow exchange between conformational substates (lifetimes > 100 ns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
194
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(209 citation statements)
references
References 93 publications
14
194
1
Order By: Relevance
“…At X-band, the spectroscopic timescale is sufficiently fast to allow different protein states to be resolved in an EPR spectrum; as a result, SDSL can be used to examine the sensitivity to osmolyte and conformational equilibria in select regions of proteins. 24 In this study, conformational exchange is demonstrated at the N-terminus of BtuB and in the Ton box of FecA. At least two motional components are found in the EPR spectra from R1 placed within the N-terminal five residues of BtuB.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…At X-band, the spectroscopic timescale is sufficiently fast to allow different protein states to be resolved in an EPR spectrum; as a result, SDSL can be used to examine the sensitivity to osmolyte and conformational equilibria in select regions of proteins. 24 In this study, conformational exchange is demonstrated at the N-terminus of BtuB and in the Ton box of FecA. At least two motional components are found in the EPR spectra from R1 placed within the N-terminal five residues of BtuB.…”
Section: Discussionmentioning
confidence: 69%
“…Protecting osmolytes are observed to have little effect upon rotameric states of R1, probably because of the small differences in solvent-exposed areas for different rotamers. 24 As a result, sensitivity to PEGs indicates that the populations in an EPR spectrum result from a protein conformational equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…1A shows a model of the L121A/L133A mutant based on the crystal structure, along with the location of R1 sensor sites and the spectra compared with those of the WT′. The spectra for the WT′ protein have been published previously and interpreted in terms of the protein structure and dynamics (16)(17)(18)(19)(20); the basic principles of spectral analysis are outlined in SI Materials and Methods. The spectra of 131R1, 132R1, 140R1, and 151R1 in the WT′ reflect a simple anisotropic motion characteristic of R1 at solvent-exposed sites in relatively rigid helical segments, whereas the spectra of 48R1, 109R1, 123R1, 128R1, and 135R1 reflect higher mobility of the nitroxide consistent with their location near or at the helix termini (16).…”
Section: Experimental Strategy and Resultsmentioning
confidence: 99%
“…1A, Inset) was introduced at solvent-exposed sites to serve as a sensor of local structure. At such sites, R1 typically has weak or no interactions with the protein, as reflected by a singlecomponent electron paramagnetic resonance (EPR) spectrum, and introduces little structural perturbation (16)(17)(18)(19). The R1 sensor Significance Analysis of protein packing reveals the prevalence of cavities, some of which are evolutionarily conserved.…”
mentioning
confidence: 99%
“…Instead, the presence of two conformations in equilibrium will, for particular locations of R1, give rise to two components in the EPR spectrum, each corresponding to one of the conformations (17,18) and of intensity proportional to the population, permitting the direct determination of the equilibrium constant. However, two-component EPR spectra can also arise from equilibrium between two rotameric states of R1 that place the nitroxide in distinct environments (19,20).…”
mentioning
confidence: 99%